Biodrying Process Efficiency: -Significance of Reactor Matrix Height. (2016) - Tom, Asha P.; Haridas, Ajit; Pawels, Renu
Abstract: Waste to energy concept should become a reality to meet the critical issues faced by the solid waste management system of developing nations. Energy oriented municipal solid waste conversion technologies have the potential to reduce the bulk volume of the waste in addition to the refuse derived fuel production applications. In this scenario biodrying process is found to be the best option, where biological heat energy is effectively channelized for drying purpose so that the heavy moisture laden municipal solid waste is dried and its energy value is increased. This technology seemed to be promising specially in the case of developing nations where the heavy moisture content of the typical municipal solid waste is the major issue faced by the waste to energy conversion systems. In the present case study the effect of increasing the reactor matrix height and the resulting changes in the biodrying process output has been studied in a pilot scale biodrying reactor of 0.565 m 3 capacity for a period of 10 days. Two case studies were conducted on mixed municipal solid waste substrates with moisture content of 62.45% and 66.4% respectively. The reactor matrix height of first case study was kept at1.65 m, while that is increased to 2.0 m in the second case study. The constant air flow rate of 40 litre per minute was provided throughout the experiment for both case studies. During the second case study an air evacuation test has also been conducted on the 4 th and 5 th day of experiment to understand the temperature profile variations. Overall weight reduction of 26.32% and 19.01% along with average moisture reduction of 24.26% and 15.98% has been achieved in the first and second case studies respectively in 10 days of reaction. The volume reduction and bulk density increase was the maximum in the second case study with 43.5% volume reduction and 53.01% bulk density increase in achieved in 10 days of biodrying reaction. Comparing to that a lesser result has been obtained in 10 days of experiment in the first case study with a volume reduction of 35.1% and bulk density increase of 27.58%. Therefore increasing the reactor matrix height at a constant air flow rate has affected the biodrying process efficiency in terms of weight reduction and moisture reduction, but the volume reduction and bulk density increase were significant achievements.